2017
DOI: 10.1016/j.compositesa.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue damage evolution in GFRP laminates with constrained off-axis plies

Abstract: ., "Fatigue damage evolution in GFRP laminates with constrained off-axis plies", Composites Part A, http://dx.doi. org/10.1016/j.compositesa.2017. method with a data mining approach and applying these to large data sets obtained during fatigue tests. It is shown that for a constant stress level, the stochastic nature of off-axis crack initiation and crack growth is accurately modelled by the Weibull distribution, with the distribution parameters being efficiently derived using the developed approach. The data-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…The underlying micro material architecture in the form of fibre-bridging, voids, varying fibre-volume fraction and varying layer thickness etc. results in significant levels of scatter of the material data points derived from fatigue tests [20]. In [20] the Weibull distribution was found to model both the stochastic nature of the crack initiation the and crack growth rates well, and provided a means for determining the stochastic material parameters.…”
Section: Fatigue Models For Off-axis Cracksmentioning
confidence: 98%
See 4 more Smart Citations
“…The underlying micro material architecture in the form of fibre-bridging, voids, varying fibre-volume fraction and varying layer thickness etc. results in significant levels of scatter of the material data points derived from fatigue tests [20]. In [20] the Weibull distribution was found to model both the stochastic nature of the crack initiation the and crack growth rates well, and provided a means for determining the stochastic material parameters.…”
Section: Fatigue Models For Off-axis Cracksmentioning
confidence: 98%
“…results in significant levels of scatter of the material data points derived from fatigue tests [20]. In [20] the Weibull distribution was found to model both the stochastic nature of the crack initiation the and crack growth rates well, and provided a means for determining the stochastic material parameters. Furthermore, it was shown that crack initiation and crack growth are not represented by a single S-N and Paris' Law master curve, but instead by S-N and crack growth Weibull fields.…”
Section: Fatigue Models For Off-axis Cracksmentioning
confidence: 98%
See 3 more Smart Citations